IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BITUNG - SIWU, ANGIE (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACT : population policy administration services stipulated in Law no. 23 of 2006 , and further elaborated in the PP . No. . 37 of 2007 and Presidential Regulation . 25 of 2008 . As a follow up of the policy then issued Regulation No. Bitung City . 5 of 2007 on the organization of registration Population and Civil Registration in Bitung , and Regulation 6 of 2007 on Population Registration Fees and Civil Registration in Bitung City , Bitung Mayor Regulation Number Number 24 Year 2008 on Details of Duties, Functions and Administration of the Department of Population and Notes civil Bitung City . This study is to answer the question of how the implementation of population policies in the service of the Department of Civil Kependudukandan Bitung City . The method used in this study is a qualitative method . The focus of the research is the implementation of " population registration services " and " the civil service " . Data source / informant research is relevant and the implementing officials at the Department of Population and Civil City of Bitung ( 9 people ) and community residents receiving services ( 4 people ) , so the total number of informants there are 13 people . Collecting data using interview techniques . The analysis technique used is the qualitative analysis of interactive models and Hubermann Miler . The results provide conclusion : ( 1 ) Implementation of service policies " resident registration " in general has done well , but the quality is not maximized ( 2 ) Implementation of service policies " civil registry " in general has done well , but the quality is also not maximized . Departing from the results of this penellian it is necessary to improving the quality of administrative services at the Department of Population and demography Civil Bitung City , among others, to improve coordination with related agencies.Keywords: demographic policy administration services.